Human language technology tools for indigenous South African languages and their potential use. - Mlambo, Respect; Matfunjwa, Muzi (Literator, 2025)
Human language technology (HLT) contributes to the development of languages by providing various avenues through which languages can be interrogated. Through HLT, diverse questions can be raised and answered scientifically and objectively. In the context of South African indigenous languages (SAIL), several HLT tools support these languages. However, it seems that some language users are unaware of the availability and capabilities of these tools, which contributes to their underutilisation. This study aims to identify and describe briefly some of the HLT tools that support and analyse SAIL. It presents an overview of the open access HLT tools, namely part-of-speech (POS) taggers, morphological decomposers (MDs), morphological analysers (MAs), isiZulu.net, ZulMorph and Google Translate (GT). These tools are crucial in analysing and understanding SAIL, as well as for advancing these languages in the field of HLT. In this study, the researchers anticipate that by raising awareness of the existence of these tools, more users of indigenous languages will be eager to use them. Contribution: This study fills the practical gap in the use of HLT to perform linguistic functions for SAIL. It seems that there is underutilisation of existing HLT tools for SAIL, which might be attributed to language users being unaware of these tools. Therefore, the study aims to identify and describe some HLT tools that support and analyse SAIL. It presents an overview of the open access HLT tools, namely POS taggers, MD, MA, isiZulu.net, ZulMorph and GT. The researchers intend to demonstrate the use of these tools and to raise awareness about their existence.